The Application of Reality Counseling as an Effort to Increase Prisoners' Resilience in Facing Negative Community Stigma - Rahmawati, Jemi; Febrian, Mochamad Fathir Wahyu; Febrianti, Widi; Muthmainah, Faliha (KnE Social Sciences, 2024)
This research is about prisoners experiencing mental disorders due to the existence of rules and laws in the community environment, which creates a negative public perception of convicts. This research aims to provide information to the general public about the magnitude of the negative stigma received by prisoners and the importance of eroding this stigma, because of the various negative impacts caused. Apart from that, this research will also comprehensively examine how big the role of reality counseling is in increasing resilience for prisoners, as well as how urgent is the counselor’s role in the resilience process. This research uses a literature study method to examine the issue of protecting the human rights of former prisoners against the negative stigma of the general public and specifically looks at Law No. 39 of 1999 concerning Human Rights. The results of this research show that there are several approaches to responding to this problem, namely the reality counseling method which acts as a means of restoring the self-confidence of former prisoners. Keywords: prisoners, reality counseling, stigma